DATA MINING ANALYSIS TO DETERMINE THE PROSPER FAMILY AREA IN SIMPANG FOUR DISTRICT WITH ALGORITHM METHOD K-MEANS CLUSTERING - Ricky Rizaldi; Fauriatun Helmiah; sudarmin (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
The long-term development phase II of Pelita VI is that development is aimed at improving the quality of Indonesia's fully developed and independent human resources. Community development is very dependent on family life which is the core part of the community, so that the family has a strategic value in national development and becomes the foundation of whole human development. The problem we face today is that there are still many families in Indonesia who are in a pre-prosperous condition, it is our obligation to improve their welfare, so as to achieve prosperous families in Simpang Empat District. It is recorded from the data that the Simpang Empat Village Hall Office has a population of 52175 people spread over twelve (12) Kelurahan with such a large population, so that there is so much data that data analysis techniques are needed to solve the problem. In this case, data mining can solve the problem of how to determine which areas/regions are classified as prosperous families I, II, and III. By clustering the variables on the number of Heads of Families according to employment status, the number of KK according to educational status, the number of Heads of Families who received capital assistance, the number of PraKS (Pre-Prosperous Family), and the number of KS1 using data mining techniques using the K-Means Clustering algorithm. Keywords: Determining Prosperous Family Area, K-Means Method, Web-Based.